Kontribusi Explosive Power Otot Tungkai Terhadap Hasil Lompat Jauh Gaya Jongkok Pada Mahasiswa Putra Prodi Pendidikan Kepelatihan Olahraga Semester II Universitas Riau - Slamet; Ali Mandan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2013)
This study employed a correlational research design aimed at determining the contribution of leg muscle explosive power to squat-style long jump performance. The research sample consisted of 42 male students from the Sports Coaching Education Study Program at Riau University. The independent variable was leg muscle explosive power, while the dependent variable was squat-style long jump performance. Data for variable X were obtained through a standing broad jump test to measure leg muscle explosive power, whereas data for variable Y were collected from squat-style long jump tests using an approach run. The data were analyzed using a normality test with the Liliefors test, followed by correlation analysis and a t-test to determine significance and contribution. The results indicated that variable X was normally distributed, while variable Y was not normally distributed. The correlation coefficient obtained was r = 0.32. The t-test results showed that t_count > t_table, indicating a significant relationship between leg muscle explosive power and squat-style long jump performance. Further analysis revealed that leg muscle explosive power contributed 10.24% to squat-style long jump performance, while the remaining 89.76% was influenced by other factors.